Treg cell plasticity as a driver of inflammation in spondyloarthritis and psoriasis - Ortega-Mejia, Ingrid Itzayanna; Romero-López, Nayeli; Casasola-Vargas, Julio César; Burgos-Vargas, Rubén; Domínguez-López, María Lilia; Romero-López, José Pablo (Frontiers in Immunology, 2025)
Regulatory T cells (Tregs) are critical for maintaining immune tolerance by suppressing effector T cell responses. However, in chronic inflammatory diseases such as spondyloarthritis (SpA) and psoriasis (PsO), Tregs can lose their stability and acquire pro-inflammatory characteristics, a phenomenon known as Treg plasticity. Under inflammatory conditions, Tregs may downregulate FoxP3, upregulate RORγt, and produce cytokines such as IL-17 and IFN-γ, thus losing their suppressive function and contributing to disease progression. In SpA, altered numbers and impaired Treg function have been identified in peripheral blood and synovial fluid. Specific subsets, such as CD161+ Tregs with Th17-like features, suggest that inflammatory cytokines and signals like STAT3 activation and ICOS engagement promote pathogenic reprogramming. Genetic factors, including HLA-B27, may further predispose Tregs to instability. Single-cell transcriptomic analyses have provided evidence of shared TCR repertoires between Tregs and effector T cells, reinforcing the concept of lineage plasticity. Similarly, in PsO, skin-resident Tregs exposed to IL-23, IL-6, and IL-21 can acquire a Th17-like phenotype, producing IL-17A and exacerbating local inflammation. Environmental factors such as hypoxia also contribute to destabilizing Treg identity. The persistence of pathogenic Tregs, even following therapy blockade of IL-17 or IL-23, highlights the challenge of achieving long-term disease remission.